HUBUNGAN POLA ASUH DAN PEMBERIAN ASI EKSKLUSIF DENGAN STATUS GIZI BAYI DI KLINIK SARGIATI Amd.Keb TAHUN 2023 - Sinaga, Suharni Pintamas; Tampubolon, Elmina (Jurnal Penelitian Kesmasy, 2024)
The focus on improving public nutrition in Indonesia remains centered on addressing the nutritional status of Indonesian children. According to the 2014 Global Nutrition Report (GNR), Indonesia is one of 17 out of 117 countries facing the triple burden of stunting, wasting, and overweight among infants or toddlers within the first days of life. Despite efforts, exclusive breastfeeding rates in Indonesia have not met the targeted 80%. In 2016, exclusive breastfeeding rates for infants aged 0-5 months were at 54.0%, while only 29.5% were exclusively breastfed up to 6 months. Although South Sumatra province has surpassed the national average with a rate of 60.4%, it still falls short of the desired 80%. Researchers focused on the Sargiati Amd clinic, particularly exploring the correlation between parenting styles, exclusive breastfeeding, and infant nutritional status. Among the 19 respondents, the majority exhibited a certain parenting style. Among them, 11 individuals had good nutritional status (36.7%), while 8 had poor nutritional status (36.7%). Only a minority (6.7%) had poor nutritional status. Surprisingly, among those with good parenting habits, the majority had poor nutritional status (23.3%), while the minority had good nutritional status (13.3%). Statistical analysis using a chi-square test with a significance level of 0.05 yielded a p-value of 0.256 (P > 0.05), indicating acceptance of the null hypothesis (Ho) and rejection of the alternative hypothesis (Ha). Thus, no significant relationship was found between parenting style and nutritional status. However, there was a significant relationship between parents' eating habits and healthy habits with nutritional status (p = 0.014; p = 0.006).